Knowledge, attitude and perceived harm of e-cigarette use behaviour among medical and dental undergraduate students in UiTM / Muhammad Faris Mahamad Sobri ... [et al.] - Mahamad Sobri, Muhammad Faris; Azlan, Adam Harith; Md. Bohari, Nor Faezah; Mohd Radzi, Nawwal Alwani; Bakri, Noor Nazahiah (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Background: Healthcare professionals have a prominent role to play in addressing the tobacco epidemic and the rapid increase of e-cigarette use in the population. The growing interest of electronic cigarettes has led to a broad debate whether e-cigarettes can be used as a harm reduction tool towards smoking. Objectives: This study aims to explore the knowledge, attitude, and perceived harm of vaping behaviour among medical and dental undergraduate students in UiTM. Methods: A questionnaire-based survey was administered using Google Form to all participants. Demographics and data from four domains of knowledge, attitude towards vaping behaviour, mass media exposure of e-cigarettes and perception of health-related risks of vaping were collected. Results: Data were obtained from 309 undergraduates with a mean age of 20.6 (SD ± 1.60). The majority of them have never smoked (96.1%) or used e-cigarettes (99.0%). Nine in 10 believe they play a role in their patient’s smoking cessation therapy in the future (91.3%). Slightly more than half (62.1%) have poor knowledge of e-cigarette, less favourable attitude towards vaping (50.8%) and perceived e-cigarettes to be less harmful (56.0%). The majority of them also claimed high exposure towards e-cigarette marketing from the mass media (85.1%). Conclusion: UiTM medical and dental undergraduates have less favourable attitudes towards e-cigarettes but lacked knowledge on the issue. They also perceived the e-cigarettes to be less harmful to health compared to conventional cigarettes. This points out the urgent need to further educate health professionals and also to provide clear guidelines at every level to regulate vaping behaviour among the population.